Prevalence of childhood polyvictimization, mental health outcomes, and associated risk and protective factors in Ethiopia and Uganda refugee settings - Stella Muthuri; George Odwe; Francis Obare; Peter Kisaakye; Dagim Habteyesus; Gloria Seruwagi; Yohannes Wado; Yadeta Bacha; Bonnie Wandera; Caroline Kabiru; Chi-Chi Undie (PLoS ONE, 2026)
Background Children exposed to polyvictimization (exposure to multiple types of victimization), experience severe impacts on health and well-being across the life course. While the prevalence, risk factors, and health consequences of polyvictimization have been well documented in lower-middle-income countries, there remains a significant knowledge gap regarding the situation in humanitarian contexts, particularly in refugee settings. Objectives We examined the prevalence, risk, and protective factors of polyvictimization and its association with mental health outcomes in refugee settings in Uganda and Ethiopia. Data and methods We utilized data from the Uganda Humanitarian Violence Against Children and Youth Survey (HVACS) 2022, which included 1,338 females and 927 males, and the Ethiopia HVACS 2024, which comprised 1,937 females and 1,536 males. These were representative, cross-sectional household surveys of females and males aged 13–24 years living in refugee settlements in Uganda and Ethiopia. Analysis entailed cross-tabulation with chi-square test and estimation of a multivariate logistic regression model. Results In both settings, males experienced higher rates of polyvictimization than females (49% vs.30% in Uganda and 33% vs. 29%. in Ethiopia). Several risk factors for childhood polyvictimization were identified at the individual level, including having a disability and endorsing intimate partner violence against women, and at the family level, such as having a difficult relationship with one’s father and household food insecurity. Conversely, living in a female-headed household was found to be protective against childhood polyvictimization across both settings. Additionally, polyvictimization was significantly associated with higher odds of mental distress, self-harm, and suicidal ideation/attempts among females and males in both Uganda and Ethiopia refugee settings. Conclusion Our findings confirm that childhood polyvictimization is prevalent among refugee populations in Uganda and Ethiopia, with nuanced insights into the risk and protective factors. The challenging circumstances within these refugee settings may exacerbate polyvictimization and its consequences. Therefore, it is essential to prioritize preventive measures alongside response strategies in addressing polyvictimization in these contexts, starting much earlier in the life course.